ANALISIS FAKTOR YANG MEMPENGARUHI ROA BANK UMUM DI INDONESIA YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) - Budi Wahyono, 10.05.52.0099; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
This study aims to determine Analysis of Factors Influencing Financial Performance of Commercial Banks Listed In Indonesia Indonesia Stock Exchange. The population in this study is a banking company that is listed on the stock exchange Indonesia 2009-2012. The sample in this study were taken by purposive sampling method. Data were analyzed using skewness-kurtosis normality test, classical assumption, koofisiendeterminasi test, F test and test hypotheses. The results of hypothesis testing the first hypothesis testing results showed that CAR is not a significant positive effect on ROA. The second hypothesis testing results showed that LDR significant positive effect on ROA. The third hypothesis testing results showed that the NPL significant negative effect on ROA. The fourth hypothesis testing results showed that no significant DER positive effect on ROA.Keywords: CAR, LDR, NPL, DER, ROA